Pengaruh Kualitas Pelayanan dan Digital Marketing Terhadap Kepuasan Pelanggan dalam Penggunaan Jasa Ekspedisi di PT Pos Indonesia (Persero) Kota Malang - Wildan Habibie Abdullah; Lina Budiarti; Musthofa Hadi (INDO PUBLISHING, 2025)
This study investigates the impact of service quality and digital marketing on customer satisfaction within the expedition service sector, focusing on PT. Pos Indonesia (Persero) Malang Branch Office. In highly competitive logistics, customer satisfaction is a critical success indicator, directly influenced by service interaction quality and effective digital promotion. The research aims to understand how PT. Pos Indonesia can enhance its service quality and optimize digital marketing strategies to improve customer satisfaction and maintain competitiveness.This study employed a quantitative approach by distributing questionnaires to customers of PT. Pos Indonesia (Persero) Malang Branch Office. The collected data were then analyzed using multiple linear regression to examine the influence of independent variables on the dependent variable. The population consisted of all customers using the company’s expedition services, with the sample selected through purposive sampling. The results indicated that both service quality and digital marketing had a positive and significant influence on customer satisfaction. Both simultaneously and individually. The coefficient of determination revealed that 77.6% of the variation in customer satisfaction was explained by the two variables, while the remaining 22.4% was influenced by other factors outside the research model. In conclusion, good service quality and effective digital marketing strategies are crucial factors in enhancing customer satisfaction at PT. Pos Indonesia (Persero) KCU Kota Malang. Therefore, the company is advised to continue investing in improving service quality, both in terms of speed, accuracy, and staff friendliness, as well as developing more innovative digital marketing strategies to reach broader market segments.